Labour dynamics and the non-government community services workforce in NSW - Cortis, Natasha; Hilferty, Fiona; Chan, Sharmi; Tannous, Kathy (UNSW Sydney, 2009)
Community service agencies work independently, together, and with governments and community members to build social relationships, promote access and participation, and ensure quality of life, especially for people experiencing hardship. The quality and effectiveness of these services depends on a high quality, capable, and sustainable workforce. Around Australia, developing and sustaining the non-government sector workforce has become a shared goal of government agencies, peak bodies, unions and employers. The research contained in this report was conducted to obtain evidence which is specific to New South Wales (NSW), and can inform local strategies for building capacity and sustainability. The project was developed in response to a request from the Department of Premier and Cabinet (DPC) and the Department of Community Services (DoCS), following the development of workforce initiatives by NSW Government Human Service CEOs and the Forum of Non-Government Agencies (FONGA) in 2008. The exploratory study consisted of four strands: a literature and data review; the NSW non-government organisation (NGO) community services workforce survey; focus groups with workers; and stakeholder interviews. Together, the strands provide vital information about the state of the non-government sector workforce, highlighting strengths and challenges, and possible strategies for reform.
Report 10/09
Keywords: Social Policy